<< Chapter < Page Chapter >> Page >

Deriving the equation of an ellipse centered at the origin

Let ( c , 0 ) and ( c , 0 ) be the foci    of a hyperbola centered at the origin. The hyperbola is the set of all points ( x , y ) such that the difference of the distances from ( x , y ) to the foci is constant. See [link] .

If ( a , 0 ) is a vertex of the hyperbola, the distance from ( c , 0 ) to ( a , 0 ) is a ( c ) = a + c . The distance from ( c , 0 ) to ( a , 0 ) is c a . The sum of the distances from the foci to the vertex is

( a + c ) ( c a ) = 2 a

If ( x , y ) is a point on the hyperbola, we can define the following variables:

d 2 = the distance from  ( c , 0 )  to  ( x , y ) d 1 = the distance from  ( c , 0 )  to  ( x , y )

By definition of a hyperbola, d 2 d 1 is constant for any point ( x , y ) on the hyperbola. We know that the difference of these distances is 2 a for the vertex ( a , 0 ) . It follows that d 2 d 1 = 2 a for any point on the hyperbola. As with the derivation of the equation of an ellipse, we will begin by applying the distance formula    . The rest of the derivation is algebraic. Compare this derivation with the one from the previous section for ellipses.

                                       d 2 d 1 = ( x ( c ) ) 2 + ( y 0 ) 2 ( x c ) 2 + ( y 0 ) 2 = 2 a Distance Formula ( x + c ) 2 + y 2 ( x c ) 2 + y 2 = 2 a Simplify expressions .                             ( x + c ) 2 + y 2 = 2 a + ( x c ) 2 + y 2 Move radical to opposite side .                               ( x + c ) 2 + y 2 = ( 2 a + ( x c ) 2 + y 2 ) 2 Square both sides .                      x 2 + 2 c x + c 2 + y 2 = 4 a 2 + 4 a ( x c ) 2 + y 2 + ( x c ) 2 + y 2 Expand the squares .                      x 2 + 2 c x + c 2 + y 2 = 4 a 2 + 4 a ( x c ) 2 + y 2 + x 2 2 c x + c 2 + y 2 Expand remaining square .                                               2 c x = 4 a 2 + 4 a ( x c ) 2 + y 2 2 c x Combine like terms .                                    4 c x 4 a 2 = 4 a ( x c ) 2 + y 2 Isolate the radical .                                        c x a 2 = a ( x c ) 2 + y 2 Divide by 4 .                                    ( c x a 2 ) 2 = a 2 [ ( x c ) 2 + y 2 ] 2 Square both sides .                      c 2 x 2 2 a 2 c x + a 4 = a 2 ( x 2 2 c x + c 2 + y 2 ) Expand the squares .                     c 2 x 2 2 a 2 c x + a 4 = a 2 x 2 2 a 2 c x + a 2 c 2 + a 2 y 2 Distribute  a 2 .                                    a 4 + c 2 x 2 = a 2 x 2 + a 2 c 2 + a 2 y 2 Combine like terms .                   c 2 x 2 a 2 x 2 a 2 y 2 = a 2 c 2 a 4 Rearrange terms .                     x 2 ( c 2 a 2 ) a 2 y 2 = a 2 ( c 2 a 2 ) Factor common terms .                               x 2 b 2 a 2 y 2 = a 2 b 2 Set  b 2 = c 2 a 2 .                              x 2 b 2 a 2 b 2 a 2 y 2 a 2 b 2 = a 2 b 2 a 2 b 2 Divide both sides by  a 2 b 2                                      x 2 a 2 y 2 b 2 = 1

This equation defines a hyperbola centered at the origin with vertices ( ± a , 0 ) and co-vertices ( 0 ± b ) .

Standard forms of the equation of a hyperbola with center (0,0)

The standard form of the equation of a hyperbola with center ( 0 , 0 ) and transverse axis on the x -axis is

x 2 a 2 y 2 b 2 = 1

where

  • the length of the transverse axis is 2 a
  • the coordinates of the vertices are ( ± a , 0 )
  • the length of the conjugate axis is 2 b
  • the coordinates of the co-vertices are ( 0, ± b )
  • the distance between the foci is 2 c , where c 2 = a 2 + b 2
  • the coordinates of the foci are ( ± c , 0 )
  • the equations of the asymptotes are y = ± b a x

See [link] a .

The standard form of the equation of a hyperbola with center ( 0 , 0 ) and transverse axis on the y -axis is

y 2 a 2 x 2 b 2 = 1

where

  • the length of the transverse axis is 2 a
  • the coordinates of the vertices are ( 0, ± a )
  • the length of the conjugate axis is 2 b
  • the coordinates of the co-vertices are ( ± b , 0 )
  • the distance between the foci is 2 c , where c 2 = a 2 + b 2
  • the coordinates of the foci are ( 0, ± c )
  • the equations of the asymptotes are y = ± a b x

See [link] b .

Note that the vertices, co-vertices, and foci are related by the equation c 2 = a 2 + b 2 . When we are given the equation of a hyperbola, we can use this relationship to identify its vertices and foci.

Questions & Answers

what is the VA Ha D R X int Y int of f(x) =x²+4x+4/x+2 f(x) =x³-1/x-1
Shadow Reply
can I get help with this?
Wayne
f(x)=x square-root 2 +2x+1 how to solve this value
Marjun Reply
what is algebra
Ige Reply
The product of two is 32. Find a function that represents the sum of their squares.
Paul
if theta =30degree so COS2 theta = 1- 10 square theta upon 1 + tan squared theta
Martin Reply
how to compute this 1. g(1-x) 2. f(x-2) 3. g (-x-/5) 4. f (x)- g (x)
Yanah Reply
hi
John
hi
Grace
what sup friend
John
not much For functions, there are two conditions for a function to be the inverse function:   1--- g(f(x)) = x for all x in the domain of f     2---f(g(x)) = x for all x in the domain of g Notice in both cases you will get back to the  element that you started with, namely, x.
Grace
sin theta=3/4.prove that sec square theta barabar 1 + tan square theta by cosec square theta minus cos square theta
Umesh Reply
acha se dhek ke bata sin theta ke value
Ajay
sin theta ke ja gha sin square theta hoga
Ajay
I want to know trigonometry but I can't understand it anyone who can help
Siyabonga Reply
Yh
Idowu
which part of trig?
Nyemba
functions
Siyabonga
trigonometry
Ganapathi
differentiation doubhts
Ganapathi
hi
Ganapathi
hello
Brittany
Prove that 4sin50-3tan 50=1
Sudip Reply
f(x)= 1 x    f(x)=1x  is shifted down 4 units and to the right 3 units.
Sebit Reply
f (x) = −3x + 5 and g (x) = x − 5 /−3
Sebit
what are real numbers
Marty Reply
I want to know partial fraction Decomposition.
Adama Reply
classes of function in mathematics
Yazidu Reply
divide y2_8y2+5y2/y2
Sumanth Reply
wish i knew calculus to understand what's going on 🙂
Dashawn Reply
@dashawn ... in simple terms, a derivative is the tangent line of the function. which gives the rate of change at that instant. to calculate. given f(x)==ax^n. then f'(x)=n*ax^n-1 . hope that help.
Christopher
thanks bro
Dashawn
maybe when i start calculus in a few months i won't be that lost 😎
Dashawn
what's the derivative of 4x^6
Axmed Reply
24x^5
James
10x
Axmed
24X^5
Taieb
comment écrire les symboles de math par un clavier normal
SLIMANE
Practice Key Terms 4

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask